The Effectiveness of Parenting Class Against Change of Mother’s Behavior in Stimulating Growth and Development of 2-5 Years Aged Toddler - Tutiek Herlina; Triana Septianti Purwanto (Humanistic Network for Science and Technology (HNST), 2018)
Children are next generation for a nation. It is expected that the children have high quality, which is indicated by healthy growth and development. However, many things were occurred in line with the children’s growth and development. People’s independence for caring their children’s health could be improved by using KIA book (mother and children’s health book). Government had organized a program for improving the use of KIA book, which was through coordinating parenting class. Moreover, this research aimed at knowing the effectiveness of parenting class against the change of mother’s behavior in stimulating 2-5 years aged toddler’s growth and development at Poncol Village, Poncol Sub-district, Magetan District, East Java Province, Indonesia. This research was pre-experimental research with one- group pretest-posttest design. The research sample was all mothers who had 2-5 years aged toddler at Poncol Village, Poncol Sub-district, Magetan District, East Java Province, Indonesia in June 2017 and they were 59 mothers. Data collection was conducted through pretest and posttest. The research instrument utilized questionnaire. Meanwhile, data analysis utilized statistic test of paired sample t test with α 0,05. The result of data analysis for the knowledge regarding stimulation that was obtained p= 0.000 was concluded that there was a significant difference of mother’s knowledge regarding stimulation of 2-5 years aged toddler’s growth and development between before and after joining parenting class. P value for stimulation practice that was obtained p= 0.000 was concluded that there was a significant difference of mother’s practice in stimulating her 2-5 years aged toddler between before and after joining parenting class. Furthermore, the conclusion was parenting class changed effectively the mother’s behavior in stimulating 2-5 years aged toddler’s growth and development at Poncol Village, Poncol Sub-district, Magetan District, East Java, Indonesia. However, it was expected for either Poncol Village or other villages in Public Health Center of Poncol area to be able to conduct parenting class continuously in order to improve mother’s behavior in stimulating her toddler’s growth and development.Keywords: Parenting class, Stimulation, Growth, Development